2007
DOI: 10.1091/mbc.e06-08-0765
|View full text |Cite
|
Sign up to set email alerts
|

R-Ras Regulates Exocytosis by Rgl2/Rlf-mediated Activation of RalA on Endosomes

Abstract: R-Ras is a Ras-family small GTPase that regulates various cellular functions such as apoptosis and cell adhesion. Here, we demonstrate a role of R-Ras in exocytosis. By the use of specific anti-R-Ras antibody, we found that R-Ras was enriched on both early and recycling endosomes in a wide range of cell lines. Using a fluorescence resonance energy transfer-based probe for R-Ras activity, R-Ras activity was found to be higher on endosomes than on the plasma membrane. This high R-Ras activity on the endosomes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 68 publications
(109 reference statements)
9
52
0
Order By: Relevance
“…Edge-An additional function of RalGEFs may be their regulation of distinct spatial activation of their GTPase substrates (27). To further investigate the role of Rgl2 in PDAC cells, we examined the subcellular localization of endogenous Rgl2 in CFPAC-I cells.…”
Section: Rgl2 Is Localized To the Leading Edge And Its Expression Is mentioning
confidence: 99%
See 1 more Smart Citation
“…Edge-An additional function of RalGEFs may be their regulation of distinct spatial activation of their GTPase substrates (27). To further investigate the role of Rgl2 in PDAC cells, we examined the subcellular localization of endogenous Rgl2 in CFPAC-I cells.…”
Section: Rgl2 Is Localized To the Leading Edge And Its Expression Is mentioning
confidence: 99%
“…All four family members are widely expressed in many tissues, but their relative abilities to activate RalA and RalB have not been investigated. The different RalGEFs may also exhibit distinct subcellular localization, leading to spatially distinct Ral activation and engagement of different effector populations (27).…”
mentioning
confidence: 99%
“…Subsequently, Ral small GTPases were linked to exocytosis in neural, epithelial, endothelial endocrinal, and pancreatic tissues (Hazelett, et al, 2011;Lopez, et al, 2008;Moskalenko, et al, 2003;Polzin, et al, 2002;Rondaij, et al, 2004;Rondaij, et al, 2008;Takaya, et al, 2007). The two mammalian Ral homologues RalA and RalB share 85% protein sequence identity, and are well conserved in evolution (van Dam & Robinson, 2006).…”
Section: Ral Small Gtpases and The Exocyst Complexmentioning
confidence: 99%
“…Previous experiments have shown that the YFP/CFP ratio of a Raichu sensor correlates with the GTP/GDP ratio (Mochizuki et al, 2001;Yoshizaki et al, 2003). Raichu sensors for Ras family GTPases (Ras, Rap1, Ral, R-Ras) (Mochizuki et al, 2001;Takaya et al, 2007), Rho family GTPases (RhoA, Rac1, Cdc42, TC10) (Itoh et al, 2002;Yoshizaki et al, 2003), and Rab family GTPase (Rab5) (Kitano et al, 2008) have been published to date.…”
Section: Raichu Sensorsmentioning
confidence: 99%